Multivesicular body and exosome pathway responses to acute exercise. Issue 3 (30th January 2020) - Garner, Ron T.; Solfest, Jessica S.; Nie, Yaohui; Kuang, Shihuan; Stout, Julianne; Gavin, Timothy P.
Abstract : New Findings: What is the central question of this study? What is the impact of acute aerobic and aerobic + resistance (concurrent) exercise on the regulation of multivesicular body formation in human skeletal muscle? What is the main finding and its importance? Gene expression for proteins associated with multivesicular body biogenesis was increased in response to concurrent exercise, and gene expression of microRNA processing (genetic information) was increased in response to aerobic and concurrent exercise. A greater understanding of the processing of multivesicular bodies in response to acute exercise may lead to novel treatments focused on intercellular communication pathways. Abstract: Regular aerobic exercise (AEx) and resistance exercise (REx) promote many beneficial adaptations. Skeletal muscle participates in intercellular communication in part through the release of myokines and extracellular vesicles including exosomes (EXOs), the latter containing mRNA, microRNA (miRNA), lipids and proteins. Exercise‐induced regulation of skeletal muscle multivesicular body (MVB) biogenesis leading to EXO formation and release is poorly understood. We hypothesized that acute exercise would increase skeletal muscle MVB biogenesis and EXO release pathways with a greater response to aerobic + resistance exercise (A+REx) than to AEx alone. Twelve sedentary, healthy male subjects exercised on a cycle ergometer for 45 min (AEx) followed by single leg, knee extensor, resistance exercise (A+REx). Vastus lateralis biopsies were obtained at rest and 1 h post‐exercise. Key components of the MVB biogenesis, EXO biogenesis and release, and miRNA processing pathways were analysed. Clathrin and Alix mRNA (MVB biogenesis) were increased by A+REx, while DICER and exportin mRNA (miRNA processing) were increased by AEx and A+REx. There were positive relationships between MVBs and miRNA processing genes following both AEx and A+REx consistent with coordinated regulation of these interrelated processes (Alix mRNA increased with Drosha, exportin and Dicer mRNA). Acute exercise increases the regulation of components of MVB and EXO pathways as well as miRNA processing components. A greater understanding of the production and packaging of skeletal muscle MVBs, EXOs and mature miRNA could lead to novel treatments focused on intercellular communication. Abstract :